2014
DOI: 10.1371/journal.pone.0116147
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Transgenes in Local Maize Varieties of Small-Scale Farmers in Eastern Cape, South Africa

Abstract: Small-scale subsistence farmers in South Africa have been introduced to genetically modified (GM) crops for more than a decade. Little is known about i) the extent of transgene introgression into locally recycled seed, ii) what short and long-term ecological and socioeconomic impacts such mixing of seeds might have, iii) how the farmers perceive GM crops, and iv) to what degree approval conditions are followed and controlled. This study conducted in the Eastern Cape, South Africa, aims primarily at addressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Ghana and South Africa have similar features in their small-scale farming systems, e.g. less than 10 m separation of maize fields and recycling of seeds 40 61 62 .…”
Section: Discussionmentioning
confidence: 99%
“…Ghana and South Africa have similar features in their small-scale farming systems, e.g. less than 10 m separation of maize fields and recycling of seeds 40 61 62 .…”
Section: Discussionmentioning
confidence: 99%
“…The iterative searches showed that while some papers of relevance to the topic (such as [28][29][30][31][32][33][34][35][36][37]) were indeed not captured in the search, these were sufficiently few not to challenge the overall findings presented here and did not address other topics than those also addressed in the reviewed literature. The iterative searches also showed that in particular, literature addressing cultural heritage impacts of GM crops in agriculture fell outside the search.…”
Section: Methodsmentioning
confidence: 99%
“…The iterative searches also showed that in particular, literature addressing cultural heritage impacts of GM crops in agriculture fell outside the search. Examples of relevant studies are [32][33][34][35][36][37]. However, even taking into account the additional papers found in the iterative searches, such studies remain few in comparison with the other impact groups (see Section 3.2).…”
Section: Methodsmentioning
confidence: 99%
“…However, the 35s promoter sequence from the Figwort mosaic virus (FMV) was not amplified for the 15 varieties. In South Africa, 10% of varieties contained genes for insect resistance and 15% were associated with herbicide tolerant events (Iversen et al, 2014). These data along with the identification of a transgenic dark seeded maize variety from Mali would suggest additional screening of maize germplasm from Mali should be conducted.…”
Section: Resultsmentioning
confidence: 94%